The role of parents in the care for adolescents suffering from emotional and behavioral problems - Mackova, Jaroslava; Veselska, Zuzana Dankulincova; Geckova, Andrea Madarasova; Jansen, Danielle E. M. C.; van Dijk, Jitse P.; Reijneveld, Sijmen A. (Frontiers in Psychology, 2022)
Background: Parents play an important role in the psychosocial care of their children. Previous research has primarily examined their role in care entry, whereas evidence on their role in other stages of the care process is scarce and lacking particularly in regard to the perspective of care providers. Our aim was therefore to examine how psychosocial care providers perceive the role of parents in the process of psychosocial care for adolescents. Methods: We used data from 25 semi-structured interviews with psychosocial care providers on the roles of parents in the care process. We analysed data using consensual qualitative research and thematic analysis. Results: Four main themes were identified: 1. parents as a source of adolescents’ problems; 2. parents trying to escape from responsibility for adolescents with problems; 3. parents as an active part of the care for adolescents; and 4. parents as a barrier to effective care. Conclusion: Psychosocial care providers should specifically address the role of the parents in psychosocial care to improve outcomes. Specific interventions are needed to support the involvement of parents in care, as their role is important. Moreover, professionals can be better trained in working with multiproblem families also to resolve some of the negative perceptions of these parents.